Characterizing Upward Lightning With and Without a Terrestrial Gamma Ray Flash. Issue 20 (16th October 2018) - Smith, D. M.; Bowers, G. S.; Kamogawa, M.; Wang, D.; Ushio, T.; Ortberg, J.; Dwyer, J. R.; Stock, M.
Abstract: We compare two observations of gamma rays before, during, and after lightning flashes initiated by upward leaders from a tower during low‐altitude winter thunderstorms on the western coast of Honshu, Japan. While the two leaders appear similar, one produced a terrestrial gamma ray flash (TGF) so bright that it paralyzed the gamma ray detectors while it was occurring and could be observed only via the weaker flux of neutrons created in its wake, while the other produced no detectable TGF gamma rays at all. The ratio between the indirectly derived gamma ray fluence for the TGF and the 95% confidence gamma ray upper limit for the gamma ray quiet flash is a factor of 1.0 × 10 7 . With the only two observations of this type providing such dramatically different results—a TGF probably as bright as those seen from space and a powerful upper limit—we recognize that weak, subluminous TGFs in this situation are probably not common, and we quantify this conclusion. While the gamma ray quiet flash appeared to have a faster leader and more powerful initial continuous current pulse than the flash that produced a TGF, the TGF‐producing flash occurred during a weak gamma ray glow, while the gamma ray quiet flash did not, implying a higher electric field aloft when the TGF was produced. We suggest that the field in the high‐field region approached by a leader may be more important for whether a TGF is produced than the characteristics of the leader itself. Plain Language Summary: Bright flashes of high‐energy radiation (gamma rays) have been seen along with some lightning, usually beamed upward into space. These terrestrial gamma ray flashes (TGFs) are so bright that someone caught in the middle of one could get a hazardous radiation dose, but that region is generally in the middle of a thundercloud where airplanes seldom go. Just a few TGFs have been seen beamed downward toward the ground. We looked at two very similar—but unusual—lightning flashes that went upward into the clouds from the top of a tower in Japan in the winter, when storms are very close to the ground. One produced an enormously bright downward TGF that paralyzed our detectors on the ground, while the other produced none at all. We find evidence that the TGF occurred because the electric field in the cloud may have been higher than it was during the lightning that did not produce radiation. We also point out that this pair of events adds to previous evidence that TGFs are an "all‐or‐nothing" sort of event rather than having a continuous range of brightness from weak to strong. Key Points: Similar upward leaders approaching a thundercloud may or may not produce a terrestrial gamma ray flash (TGF) The upper limit on gamma ray fluence from one flash with no TGF is 10 7 times lower than the inferred TGF fluence from a similar flash Only the TGF‐producing leader happened during a gamma ray glow, implying a higher preexisting in‐cloud field when TGFs occur